Improved dielectric model for polyvinyl alcohol-water hydrogel at microwave frequencies - Kok, Yeow You; Abbas, Zulkifly; Khalid, Kaida; Ab. Rahman, Mohamad Zaki (Science Publications, 2010)
Problem statement: The study described rigorous dielectric modeling for Polyvinyl Alcohol (PVA)-water hydrogel mixture at microwave frequencies. Approach: A commercial openended coaxial sensor was used to measure the dielectric constant, loss factor and ionic conductivity, σ of PVA-water hydrogel mixture ranging concentration of 80-100% water content. Results: The sensor was operating between 0.13 and 20 GHz at and above of room temperature (25±1)°C. Indirectly, the relaxation time, τ, activation energy, Q and entropy change, ΔS of the hydrogel mixtures are determined based on linear fitting of measured data using Debye and Arrhenius approaches. Conclusion/Recommendations: Two main relaxation processes were found ranging 2-10 and 10-20 GHz, respectively. Dielectric dispersion is suggested to describe by combination of Cole-Davidson (CD) and Debye (Dy) processes. The results are discussed qualitatively based on bound states of water in hydrogel mixtures.